The Exception Is the Rule: Underestimating and Overspending on Exceptional Expenses - Sussman, Abigail B.; Alter, Adam L. (Journal of Consumer Research, 2012)
Abstract Purchases fall along a continuum from ordinary (common or frequent) to exceptional (unusual or infrequent), with many of the largest expenses (e.g., electronics, celebrations) being the most exceptional. Across seven studies, we show that, while people are fairly adept at budgeting and predicting how much they will spend on ordinary items, they both underestimate their spending on exceptional purchases overall and overspend on each individual purchase. Based on the principles of mental accounting and choice bracketing, we show that this discrepancy arises in part because consumers categorize exceptional expenses too narrowly, construing each as a unique occurrence and consequently overspending across a series of discretely exceptional expenses. We conclude by proposing an intervention that diminishes this tendency by helping consumers consider their spending on exceptional items as part of a larger set of purchases.